ENHANCING COGNITIVE LITERACY THROUGH LOCAL WISDOM-BASED WRITING TASK - Azizah, Siti; Mustofa, Ali (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
In the dynamic landscape of English as a foreign language education, there is a growing imperative to develop pedagogical approaches that are not only linguistically effective but also culturally inclusive. Addressing this critical need, this study investigated the effectiveness of a local wisdom-based writing task approach in cultivating cognitive literacy among English Department students. The study employed a mixed-methods design, utilizing open-ended and closed-ended questionnaires after intervention. Findings revealed that the integration of local wisdom significantly enhanced student engagement and motivation. Furthermore, the approach effectively fostered the development of cognitive literacy skills, including critical thinking, creativity, and metacognition. Students demonstrated improved planning, organization, and self-reflection in their writing processes. These findings suggest that incorporating local wisdom into task-based writing can be an effective pedagogical approach for enhancing both writing proficiency and cognitive literacy among university students.